Effects of Smoking on Inflammatory Markers in a Healthy Population as Analyzed via the Gut Microbiota - Yan, Su; Ma, Zhonghui; Jiao, Mengfan; Wang, Youxiang; Li, Ang; Ding, Suying (Frontiers in Cellular and Infection Microbiology, 2021)
The number of people who smoke has increased in recent years, and the incidence of smoking-related diseases increases annually. This study was conducted to explore whether smoking affects diseases via changes in the gut microbiota. We enrolled 33 smokers and 121 non-smokers. We collected fecal samples from all participants and performed whole-genome sequencing. Smoking significantly affected the gut microbiota. At the phylum through genus levels, the smokers’ microbiotas showed slight changes compared with those of the non-smokers. The α- and β-diversities differed significantly between the smokers and non-smokers, and the smokers’ gut microbiota compositions differed significantly from those of the non-smokers. At the species level, the relative abundances of Ruminococcus gnavus (P=0.00197) and Bacteroides vulgatus (P=0.0468) were significantly greater in the smokers than in the non-smokers, while the relative abundances of Faecalibacterium prausnitzii (P=0.0000052) and Akkermansia muciniphila (P=0.0057) were significantly lower in the smokers. Smoking increases inflammation in the body by inducing an increased abundance of proinflammatory bacteria. Non-smokers had higher abundances of anti-inflammatory microorganisms than did smokers; these microorganisms can produce short-chain fatty acids, which inhibit inflammation.